Clinical periodontal status and gingival crevicular fluid cytokine profile among cigarette-smokers, electronic-cigarette users and never-smokers. (June 2019) - BinShabaib, Munerah; ALHarthi, Shatha Subhi; Akram, Zohaib; Khan, Junad; Rahman, Irfan; Romanos, Georgios E.; Javed, Fawad
Highlights: Periodontal status and GCF cytokines among cigarette-smokers, e-cigarette users and never-smokers were compared. 46 cigarette-smokers, 44 e-cigarette users and 45 never-smokers were included. Periodontal status is poorer in cigarette-smokers compared with other groups. GCF cytokines are higher in cigarette-smokers compared with other groups. Abstract: Objective: There are no studies that have compared the clinical (plaque index [PI], bleeding on probing [BOP], probing depth [PD], clinical attachment loss [AL] and number of missing teeth [MT]) and radiographic (marginal bone loss [MBL]) periodontal parameters and gingival crevicular fluid (GCF) levels of proinflammatory cytokines among cigarette-smokers and individuals using electronic-cigarettes. The aim was to compare the clinical periodontal status and gingival crevicular fluid (GCF) cytokine profile among cigarette-smokers (Group-1), electronic-cigarette users (Group-2) and never-smokers (Group-3). Methods: Demographic data including age, gender, duration and reason for smoking and vaping and daily frequency and duration of smoking and vaping was collected using a questionnaire. Clinical (PI, BOP, PD and clinical AL) and radiographic (MBL) periodontal parameters were recorded. The volume of collected GCF was determined and levels of interleukin (IL) 1β, IL-6, tumour-necrosis-factor-alpha (TNF-α), matrix metalloproteinase (MMP)-8 and interferon-gamma (IFN-γ) were investigated. Results: Forty-six cigarette-smokers, 44 electronic-cigarette users and 45 never-smokers were included in groups 1–3, respectively. Mean scores of PI (P < 0.05), PD (P < 0.05) and clinical AL (P < 0.05) were significantly higher among individuals in Group-1 than Group-3. Compared with groups 1 (P < 0.05) and 2 (P < 0.05), BOP was more often manifested among patients in Group-3. Compared with Group-3, MBL was significantly higher in groups 1 (P < 0.01) and 2 (P < 0.01). GCF volume was significantly higher in Group-1 compared with groups 2 and 3. The concentrations of IL-1β, IL-6, IFN-γ, TNF-α and MMP-8 were significantly higher in the GCF samples of individuals in Group-1 (P < 0.05) than groups 2 and 3. Conclusion: Periodontal status is poorer and GCF levels of proinflammatory cytokines are higher in cigarette-smokers compared with electronic-cigarette smokers and never-smokers. However, the probability of increased periodontal inflammation and GCF proinflammatory cytokine levels in electronic-cigarette users than never-smokers cannot be annulled.